2018
DOI: 10.1111/cag.12442
|View full text |Cite
|
Sign up to set email alerts
|

“Power to the people”: Contesting urban poverty and power inequities through open GIS

Abstract: Key MessagesHigh costs and non-intuitive design of proprietary GIS software pose barriers to marginalized communities.Free and open source GIS provide unique access opportunities. Open GIS-based community information systems act as an alternative to proprietary GIS.Geospatial technologies are central to spatial decision making and governance, but gaining equitable access to these is still difficult for traditionally marginalized communities. We contend that the dominance of proprietary GIS software has contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Indeed, there have been increased calls for moving beyond post-post-positivistic geospatial research and toward more mixed and qualitative methods (Elwood & Cope, 2009; Lubienski & Lee, 2017; Yoon & Lubienski, 2018), as well as the application of critical perspectives in GIS research (Hogrebe & Tate, 2012; Jabbar et al, 2017; Yoon, Gulson, & Lubienski, 2018). Those calls are now being answered, and more qualitative GIS studies have emerged (Bell, 2007; Jabbar et al, 2017; Yoon, Lubienski, & Lee, 2018), including “participatory GIS” (Dunn, 2007; Elwood, 2006; Weiner & Harris, 2008; Yoon & Lubienski, 2018), those that engage marginalized communities and their members (Ghose & Welcenbach, 2018; Hogrebe & Tate, 2012; Kwan & Ding, 2008), or those that are emancipatory in nature (Sui, 2015). Mixed-method approaches invite both etic and emic perspectives, giving deeper accounts of “place” and pushing GIS research to consider not only multiple ways of knowing but also multiple ontologies.…”
Section: Overview Of Gis Analytic Techniquesmentioning
confidence: 99%
“…Indeed, there have been increased calls for moving beyond post-post-positivistic geospatial research and toward more mixed and qualitative methods (Elwood & Cope, 2009; Lubienski & Lee, 2017; Yoon & Lubienski, 2018), as well as the application of critical perspectives in GIS research (Hogrebe & Tate, 2012; Jabbar et al, 2017; Yoon, Gulson, & Lubienski, 2018). Those calls are now being answered, and more qualitative GIS studies have emerged (Bell, 2007; Jabbar et al, 2017; Yoon, Lubienski, & Lee, 2018), including “participatory GIS” (Dunn, 2007; Elwood, 2006; Weiner & Harris, 2008; Yoon & Lubienski, 2018), those that engage marginalized communities and their members (Ghose & Welcenbach, 2018; Hogrebe & Tate, 2012; Kwan & Ding, 2008), or those that are emancipatory in nature (Sui, 2015). Mixed-method approaches invite both etic and emic perspectives, giving deeper accounts of “place” and pushing GIS research to consider not only multiple ways of knowing but also multiple ontologies.…”
Section: Overview Of Gis Analytic Techniquesmentioning
confidence: 99%
“…It is worth exploring what types of participatory politics are already emerging around GIS. This includes, for instance, the idea of open-source sharing of geospatial software (Ghose & Welcenbach, 2018) and what is termed public participation GIS, in which the software and the practices and input using GIS are provided as part of community organizing projects.…”
Section: Participatory Gis: Expertise and New Policy Actorsmentioning
confidence: 99%
“…For example, Ghose and Welcenbach (2018) outlined the use of public participation GIS by schools in Milwaukee, where students from areas of poverty were trained as citizen scientists by people working on community garden projects. These authors concluded, "While there is no technological fix towards resolving poverty, open GIS can bridge the GIS digital divide, enabling marginalized communities to formulate spatial strategies in their contestations against hunger, poverty, and deprivation" (p. 79).…”
Section: Participatory Gis: Expertise and New Policy Actorsmentioning
confidence: 99%
“…Amplifying the calls to move beyond platforms and tools provided by commercial vendors, and to develop a healthy free and open source software (FOSS) ecosystem is a key consideration for Gieseking. Ghose and Welcenbach () echo this, demonstrating how the reliance upon proprietary software and training has contributed to a digital geospatial divide. Noting the central role GIS and spatial analysis play in distributing power and knowledge claims within policy and planning environments, they call for scholars to take greater care of the political economy that shapes access to and ability with spatial analysis and visualization systems.…”
mentioning
confidence: 97%